Find y prime through implicit differentiation: $\displaystyle x^2+xy-y^2 = 4$ $\displaystyle 2x+(y+xy')-2yy' = 0$ Is this step correct? And if so, where do I go from here?
Follow Math Help Forum on Facebook and Google+
Originally Posted by Open that Hampster! Find y prime through implicit differentiation: $\displaystyle x^2+xy-y^2 = 4$ $\displaystyle 2x+(y+xy')-2yy' = 0$ Is this step correct? And if so, where do I go from here? Yup, just solve for y' as if this were an algebra problem.
View Tag Cloud